2019
DOI: 10.1007/s11056-019-09762-5
|View full text |Cite
|
Sign up to set email alerts
|

Sprouts of shoot-clipped oak (Quercus alba and Q. robur) germinants show morphological and photosynthetic acclimation to contrasting light environments

Abstract: Sprouting by woody plants can increase species resilience to disturbance and foster regeneration during periods with little recruitment from seed. Though sprouting often plays a critical role in oak forest regeneration, there is little information available on sprouting capacity and sprout physiology at the seedling stage, particularly for new germinants. This study compared sprouting capacity and sprout photosynthesis of shoot-clipped germinants of two temperate oaks established in contrasting light environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…The light roofs of the climate chambers were adjusted in height so that light intensity at canopy height was in all chambers ~390 µmol m −2 s −1 . At this light intensity, all three species are at, or approach their light saturation point (Čater & Kobler, 2017 ; Pena‐Rojas et al, 2004 ; Petersson et al, 2020 ; Staudt et al, 2003 ). All plants were regularly (i.e., every 2–3 days) watered by hand to ensure complete soil hydration, and soil volumetric water content (VWC) was manually measured bi‐weekly to ensure no soil drought occurred (Supporting Information: Figure S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The light roofs of the climate chambers were adjusted in height so that light intensity at canopy height was in all chambers ~390 µmol m −2 s −1 . At this light intensity, all three species are at, or approach their light saturation point (Čater & Kobler, 2017 ; Pena‐Rojas et al, 2004 ; Petersson et al, 2020 ; Staudt et al, 2003 ). All plants were regularly (i.e., every 2–3 days) watered by hand to ensure complete soil hydration, and soil volumetric water content (VWC) was manually measured bi‐weekly to ensure no soil drought occurred (Supporting Information: Figure S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…trees following fire in central Europe was notably high and almost unaffected by fire intensity. A recent greenhouse experiment revealed that seedlings of Q. robur responded similarly to the fire adapted North American white oak (Q. alba L.) when they experienced shoot destruction typically sustained during fire (Petersson, Löf, Jensen, Chastain, & Gardiner, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…trees following fire in central Europe was notably high and almost unaffected by fire intensity. A recent greenhouse experiment revealed that seedlings of Q. robur responded similarly to the fire adapted North American white oak ( Q. alba L.) when they experienced shoot destruction typically sustained during fire (Petersson, Löf, Jensen, Chastain, & Gardiner, ). Together, these findings suggest that European temperate oak species ( Q. robur and Q. petraea) may respond to fire in a similar fashion as their North American congeners.…”
Section: Introductionmentioning
confidence: 99%